Penentuan Sub Sektor Unggulan Pada Sektor Pertanian di Kabupaten Tapanuli Selatan - Rini Lubis (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Purpose of economic growth is to spread income equality and mitigate the unemployment rate, but an obstacle to economic growth is the lack of public education that will ultimately affect the income received by the public and also increase the speed of growth of the poverty level, then it is necessary the efforts to increase people's income by having specialization of the commodities. South Tapanuli is an agricultural area where agricultural sector is the biggest contributor to the GDP. To find out the commodity especially in the agricultural sub-sector that is necessary to has LQ analysis method where this method aims to determine which commodities are superior and inferior. From the results of the analysis by LQ methods, commodities on the agricultural sub-sector based in the South Tapanuli District are a soybeans, peanuts, rice paddy and rice fields.